Promoting postgraduate programmes: AAGBS at key education and career events - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
From 20 to 25 August 2024, Arshad Ayub Graduate Business School (AAGBS), Universiti Teknologi MARA (UiTM) actively participated in a series of Postgraduate Programmes promotion activities through several major national education and career events. These included the AEROSPACE SUMMIT 2024 on 20 and 21 August 2024 at the Malaysia International Trade & Exhibition Centre (MITEC), Kuala Lumpur (Hall 5, Level 2), as well as the STAR EDUCATION FAIR 2024 and the MEGA CAREERS & STUDY FAIR 2024, both held on 24 and 25 August 2024 at Pavilion Bukit Jalil Exhibition Centre and Kuala Lumpur City Centre (KLCC) respectively. These platforms provided AAGBS with valuable opportunities to engage with prospective students, working professionals, and industry representatives, allowing the School to showcase its wide range of postgraduate programmes, academic strengths, and career-oriented learning pathways. Visitors were able to receive first-hand information on programme offerings, entry requirements, and the unique learning experience at AAGBS. Sincere appreciation is extended to the dedicated Academic Staff who represented AAGBS during these events - Assoc. Prof. Dr. Mohamad Nizam Jaafar, Dr. Zurina Ismail, Dr. Hamidah Md Yusop, and Dr. Alisa Ibrahim - for their commitment and contributions in promoting AAGBS and strengthening its visibility at the national level.